Clinical application of the 2011 IFCPC colposcope terminology - Bei Zhang; Shuhui Hong; Guihui Zhang; Fengnian Rong (BMC, 2021)
Abstract Background Colposcopy offers an accurate way to the diagnose of cervical precancerous lesions. However, the diagnostic accuracy of colposcopy is unsatisfied. This study was to evaluate colposcopic accuracy according to the 2011 International Federation of Cervical Pathology and Colposcopy (IFCPC) terminology. Methods A retrospective cohort study was performed in 1,838 patients who underwent colposcopy in Shandong Qianfoshan Hospital, Cheeloo College of Medicine, Shandong University from October 2013 to April 2018. Using conization or cervical biopsy pathology as the gold standard, the agreement between colposcopic diagnosis and pathologic diagnosis was calculated, and correlations between variables were analyzed. Results As an authoritative and widely used terminology for colposcopy diagnosis, the 2011 IFCPC terminology has certain clinical practicality and diagnostic accuracy. However, some signs such as mosaic, punctation, sharp border, inner border sign and ridge sign had high specificity but unsatisfactory sensitivity, which limited the diagnostic value. Therefore, we discussed the Lugol's staining, a very common sign in colposcopy, and analyzed the diagnostic significance of bright yellow staining in low-grade squamous intraepithelial lesion (LSIL) and mustard yellow staining in high-grade squamous intraepithelial lesion (HSIL). The results showed that mustard yellow may be a valuable indicator in the diagnosis of HSIL. Conclusion The 2011 IFCPC colposcope terminology has standardized interpretations of the colposcopic findings and improved the accuracy of colposcopy diagnosis. The aceto-white epithelium still has important diagnostic value; however, the value of a few signs is needed to be discussed and new signs are expected to be discovered. Although the significance of Lugol's staining was diminishing, mustard yellow might be a valuable indicator for the diagnosis of HSIL.